2020
DOI: 10.3389/fonc.2020.01455
|View full text |Cite
|
Sign up to set email alerts
|

Soluble PD-L1 as a Predictor of the Response to EGFR-TKIs in Non-small Cell Lung Cancer Patients With EGFR Mutations

Abstract: Programmed cell death ligand 1 (PD-L1) expressed on tumor tissues is a vital molecule for immune suppression and its impact on the response to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) has been reported. The significance of soluble PD-L1 (sPD-L1) for lung cancer patients remains unknown. This study investigated whether sPD-L1 could predict the response of EGFR-mutated non-small cell lung cancer (NSCLC) to EGFR-targeted therapy. We retrospectively evaluated patients who received fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…In most cases, the level of circulating sPD-L1 was found to be enhanced in the plasma of patients with the indicated pathology compared to healthy control (see Table 1 . For the oncology indications, the presence of sPD-L1 and its significance are discussed in the following studies: AEC [ 41 ]; BTC [ 42 , 43 ]; brain tumors [ 26 , 44 ]; CRCC [ 45 , 46 ]; CRC [ 47 ]; cutaneous melanoma [ 48 ]; DLBCL [ 49 , 50 ]; EOC [ 51 , 52 ]; ENKTL [ 53 , 54 ]; HNSCC [ 36 ]; HCC [ 55 , 56 , 57 ]; HL [ 54 , 58 ]; mesothelioma [ 59 , 60 ]; NC [ 61 , 62 ]; PGC [ 63 , 64 , 65 ]; NSCLC [ 66 , 67 ]; PC [ 68 ]; PCNSL [ 50 ]; STS [ 69 , 70 ]; TC [ 71 ]; TNBC [ 72 ]; WM [ 73 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, the level of circulating sPD-L1 was found to be enhanced in the plasma of patients with the indicated pathology compared to healthy control (see Table 1 . For the oncology indications, the presence of sPD-L1 and its significance are discussed in the following studies: AEC [ 41 ]; BTC [ 42 , 43 ]; brain tumors [ 26 , 44 ]; CRCC [ 45 , 46 ]; CRC [ 47 ]; cutaneous melanoma [ 48 ]; DLBCL [ 49 , 50 ]; EOC [ 51 , 52 ]; ENKTL [ 53 , 54 ]; HNSCC [ 36 ]; HCC [ 55 , 56 , 57 ]; HL [ 54 , 58 ]; mesothelioma [ 59 , 60 ]; NC [ 61 , 62 ]; PGC [ 63 , 64 , 65 ]; NSCLC [ 66 , 67 ]; PC [ 68 ]; PCNSL [ 50 ]; STS [ 69 , 70 ]; TC [ 71 ]; TNBC [ 72 ]; WM [ 73 ].…”
Section: The Pd-1/pd-l1 Checkpointmentioning
confidence: 99%
“…For examples, in locally advanced non-small cell lung cancer (NSCLC), a median serum sPD-L1 concentration of 67–68 pg/mL has been reported [ 66 , 122 ], whereas other studies indicated median sPD-L1 levels of 27 pg/mL [ 123 ], 84 pg/mL [ 124 ] and 176 pg/mL [ 125 ]. Moreover, much higher values have been reported with other methods, up to 568 pg/mL measured using a multiplex assay [ 67 ] and 3.84 ng/mL measured with another ELISA procedure [ 126 ]. A quantitative comparison is thus difficult, if not impossible.…”
Section: Significance Of Soluble Pd-l1 In Cancermentioning
confidence: 99%
“…NSCLC patients with EGFR mutation had higher sPD-L1 levels compared to wild type and a post-therapeutic significant reduction in sPD-L1 level was only observed in EGFR mutated patients ( 210 ). In a separate study, NSCLC patients receiving anti-EGFR treatment showed a median 19.19% change in the pre-treatment and on-treatment sPD-L1 level; though, there was no differences in the treatment response or progression free survival between patients with or without a reduction of sPD-L1 levels ( 211 ). Further exploration would be required to identify the cause of reduction in sPD-L1 levels after EGFR treatment and to establish its association with cancer prognosis.…”
Section: Pd-1 Inhibitory Checkpoint Molecules Axismentioning
confidence: 99%
“…The circulatory cell expressing PD-L1 still retains its biological activity, and it can specifically bind the PD-1 receptor of the T cells in peripheral blood, thereby activating the PD-1/PD-L1 pathway and establishing systemic immunosuppression ( 6 , 7 ). Moreover, sPD-L1 is a prognostic marker of tumor treatment ( 8 ).…”
Section: Introductionmentioning
confidence: 99%